Pelatihan Start Up KEDIP dan Up Skill Scale Program Dalam upaya Upgrading UMKM Desa Beralih ke Digital - Suprayitno, Nur Fadillah; Rachmat, Zul (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Business and digital are interrelated, as is the use of existing technology to run and develop a business. In this digital era, marketing is not only done offline but is starting to switch to digital marketing. Doing digital marketing by utilizing social media and the marketplace. This training program aims to assist businessmen in the regions and districts in utilizing digital technology. The method of implementing this activity includes coordination of activities, preparation of tools, implementation, and evaluation. This training activity was held on the STMIK AMIKA Soppeng campus with speakers by M. Adnan Aries, CEO and Founder of Start Up KEDIP, with the target audience of students who want to increase their knowledge and quality of human resources. The conclusion obtained from the survey results of training activities is that the training has been carried out properly.